2021
DOI: 10.1155/2021/6669754
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and Physicochemical Quality of Drinking Water in Adis Kidame Town, Northwest Ethiopia

Abstract: Drinking water pollution and the resulting waterborne diseases have been among the major public health burden in low-income countries such as Ethiopia. A high prevalence of waterborne diseases, up to 65%, has been reported in Adis Kidame Town (Ethiopia). Moreover, there have been poor waste disposal practices in this town. Thus, this study aimed to assess bacteriological and physicochemical drinking water quality in Adis Kidame Town to get insight into any potential health risks due to waterborne diseases. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…To that end, with the exception of some hand washing facilities in Wonago woreda (15.8%), none of the other woredas' hand washing facilities met the WHO guideline of less than 0.2 mg/l. This is consistent with the findings of a study conducted in Ethiopia's Addis Ketema woreda, which found that the concentration of residual chlorine in 96.7% of samples was below the normal range (0.2 mg/L-0.5 mg/L) [23].…”
Section: Resultssupporting
confidence: 92%
“…To that end, with the exception of some hand washing facilities in Wonago woreda (15.8%), none of the other woredas' hand washing facilities met the WHO guideline of less than 0.2 mg/l. This is consistent with the findings of a study conducted in Ethiopia's Addis Ketema woreda, which found that the concentration of residual chlorine in 96.7% of samples was below the normal range (0.2 mg/L-0.5 mg/L) [23].…”
Section: Resultssupporting
confidence: 92%
“…Out of the total samples collected from the households, 15% were not met the recommended pH range. Turbidity deteriorates the physical quality and acceptance of drinking water as well contributes to the alteration of colour, odour and taste of the water (WHO 2021; Mohammed and Abdulrazzaq 2018;Sitotaw and Geremew 2021). All the sampled tap water met both the WHO and national standard (< 5NTU) while 5 (8.3%) of household water samples had turbidity above the standards.…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…In some parts of Ethiopia, drinking water quality studies were conducted by sampling different water supply sources and water from taps of the end-users. Most of the findings indicated that microbial and physicochemical characteristics of the waters were poor and below national and international water quality standards (Kassegne and Leta 2020;Gizachew et al 2020;Werkneh et al 2015;Yasin et al 2015a;Sitotaw and Geremew 2021;Duressa et al 2019;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking water can be contaminated at any point along the supply chain, from the source to the household container, and contaminated water can carry a variety of viruses. As a result, 80 % of the world's population is affected by water-related diseases, and around 2billion people drink feces-contaminated water, resulting in an estimated 485,000 diarrhoeal fatalities per year (Sitotaw & Geremew, 2021).…”
Section: Introductionmentioning
confidence: 99%